2011
DOI: 10.1179/174313211x12966635733277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium chloride on psychomotor activity, emotional status, and acute behavioural responses to clonidine,d-amphetamine, arecoline, nicotine, apomorphine, and L-5-hydroxytryptophan

Abstract: Combination of Mg salts and pyridoxine hydrochloride can be effective at treating some behavior form of primary Mg deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 48 publications
0
17
0
8
Order By: Relevance
“…However, the two groups had no difference in regard to cardiopulmonary bypass items, surgical variables, or anesthetic parameters; this indicated that the underlying clinical situations for the study were largely identical in the two groups. Magnesium may 'modulate cellular inflammation' while 'suppressing the inflammatory role of inflammatory cells and cytokines' (34, 35) through the 'activation of N-methyl-d-aspartate (NMDA) receptors', 'phosphoinositide 3-kinase/Akt pathway' and suppression of inflammatory neuromediators through the activation of 'neuro-endocrinological pathways' as the main mechanisms; since, magnesium is a natural antagonist of calcium ion (3-6, 30, 35-37, 42). The inflammatory response after CBP is one of the most significant side effects of this surgical intervention, and a number of compensatory mechanisms and approaches have been proposed, though many remain equivocal (1, 2, 10, 12, 27, 45-49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the two groups had no difference in regard to cardiopulmonary bypass items, surgical variables, or anesthetic parameters; this indicated that the underlying clinical situations for the study were largely identical in the two groups. Magnesium may 'modulate cellular inflammation' while 'suppressing the inflammatory role of inflammatory cells and cytokines' (34, 35) through the 'activation of N-methyl-d-aspartate (NMDA) receptors', 'phosphoinositide 3-kinase/Akt pathway' and suppression of inflammatory neuromediators through the activation of 'neuro-endocrinological pathways' as the main mechanisms; since, magnesium is a natural antagonist of calcium ion (3-6, 30, 35-37, 42). The inflammatory response after CBP is one of the most significant side effects of this surgical intervention, and a number of compensatory mechanisms and approaches have been proposed, though many remain equivocal (1, 2, 10, 12, 27, 45-49).…”
Section: Discussionmentioning
confidence: 99%
“…Since, magnesium is a natural antagonist of calcium ion and MgSO4, which acts through inhibition of 'N-methyl-D-aspartate dependent cellular pathways'(3-6, 30, 35, 36). On the other hand, it has been demonstrated that decreased plasma levels of magnesium can activate inflammatory neuromediators via the activation of 'neuroendocrinological pathways (37). At the same time, other studies have demonstrated that NF-kappaB activation with simultaneous suppression ofendotoxin, induces an increase in inflammatory mediators due to magnesium infusion in animals; furthermore, these mechanisms possibly work in a similar way in coronary artery bypass graft (CABG) patients (3-6, 34, 38-43).…”
Section: Objectivesmentioning
confidence: 99%
“…To evaluate the Mg concentration, a two ml sample of heparinized venous blood was collected every week from the sublingual vein while the rats were under isoflurane anaesthesia [42]. RBC and plasma Mg levels were measured via a previously described colorimetric assay method in which Mg is stained using thiazole yellow [43]. After Mg concentration in rats fed the low Mg diet had decreased, the animals were treated with one of the following supplementations: Mg L-aspartate, Mg N-acetyltaurate, Mg chloride or Mg sulphate (50 mg of elementary Mg per kg body weight for 14 days).…”
Section: Oxidative Stress and Magnesium Deficiencymentioning
confidence: 99%
“…Blood plasma and brain Mg levels are also significantly correlated with anxiety-related behavioral responses in rodents [44]. Supplementing Mg levels in mice has been demonstrated to reduce the expression of anxiety-related behavior [30,45]. …”
Section: Introductionmentioning
confidence: 99%